Does Video-Assisted Thoracoscopic Surgery with Bullectomy and Partial Pleurectomy for Primary Spontaneous Pneumothorax Impair Health-Related Quality of Life and Pulmonary Function? - Stephen Fung (MDPI AG, 2021)
Background: Video-assisted thoracoscopic surgery (VATS) with partial pleurectomy is an established treatment for primary spontaneous pneumothorax (PSP). However, postoperative pulmonary function and health-related quality of life (HR-QoL) after VATS–bullectomy with partial pleurectomy (VBPP) have not been elucidated. Methods: Eligible patients were assessed for HR-QoL using the Short-Form 36 (SF-36) health survey. Pulmonary function (PF) was evaluated by spirometry. We compared the results of the VBPP cohort with the German national norms, and with a similar cohort of patients successfully treated by chest tube (CT) only. Results: A total of 25 VBPP patients completed the SF-36 health survey, of whom 15 presented for PF assessment. Between the VBPP and CT groups, the mean forced vital capacity (FVC), forced expiratory volume in one second (FEV1), and FEV1/FVC ratio were not statistically significantly different. However, in both groups, FVC, FEV1, and FEV1/FVC were above the lower limit of normal (LLN), suggesting no restrictive or obstructive patterns. Compared with the sex- and age-matched normal German population, patients who underwent VBPP displayed a similar physical component summary score and a significantly decreased mental component summary score. Interestingly, comparison of the SF-36 domains between the VBPP and CT groups showed no statistical difference. Conclusion: VBPP is a suitable surgical treatment for PSP, with no apparent adverse impacts on pulmonary or physical function. However, psychological distress and measures to counteract its impact should be considered.